2020
DOI: 10.1111/aphw.12201
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Health Action Process Approach and mHealth Intervention to Increase Non‐Sedentary Behaviours in Office‐Working Adults—A Randomised Controlled Trial

Abstract: Background: Office-working adults represent an at-risk population for high levels of sedentary behaviour (SB), which has been associated with an increased risk for numerous chronic diseases. This study examined the effectiveness of a Health Action Process Approach (HAPA) based planning intervention augmented with tailored text messages to reduce workplace sitting time (primary outcome) and increase specific non-SBs (i.e. standing time, walking time, stretching time, break frequency, break duration). A secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…Mobile health intervention might be useful means to prompt individuals perform health behaviors. These self-regulation-based interventions effectively improved other health behaviors (Poppe et al, 2019 ; Rollo & Prapavessis, 2020 ). Future research can confirm the potential of these interventions in promoting facemask wearing and hand washing.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile health intervention might be useful means to prompt individuals perform health behaviors. These self-regulation-based interventions effectively improved other health behaviors (Poppe et al, 2019 ; Rollo & Prapavessis, 2020 ). Future research can confirm the potential of these interventions in promoting facemask wearing and hand washing.…”
Section: Discussionmentioning
confidence: 99%
“…The HAPA model is frequently used for the promotion of PA [15,21,23] in both clinical [24,25] and non-clinical populations. The model is generic and flexible, and can easily be applied to several behaviours [26] such as dietary behaviour [19,26], sunscreen use [27], and sedentary behaviour [28][29][30]. Therefore we chose to focus on the BCTs 'action planning', 'coping planning' and 'self-monitoring' for both PA and SB.…”
Section: Introductionmentioning
confidence: 99%
“…The literature supports the notion that sedentary behaviour and physical activity are distinct, interdependent constructs, and our findings further highlight the need to understand the applicability of behaviour change theories to sedentary behaviour (Rhodes et al, 2012). Although some previous studies have demonstrated the efficacy of a HAPA planning intervention in addressing sedentary behaviour (Rollo and Prapavessis, 2020), it is possible the HAPA model may be more amenable to beginning new behaviours rather than ceasing problematic behaviours. For instance, interventions promoting physical activity participation target starting a new behaviour, while the reduction of sedentary behaviour requires individuals to stop engaging in potentially harmful behaviour very much 'baked in' to contemporary society, and may require environmental or institution-level interventions in addition to targeting change at the individual level.…”
Section: Hapa and Behavioural Outcomesmentioning
confidence: 99%